Effects of Nanoparticles on Algae: Adsorption, Distribution, Ecotoxicity and Fate - Feng Wang; Wen Guan; Ling Xu; Zhongyang Ding; Haile Ma; Anzhou Ma; Norman Terry (Applied Sciences, 2019)
With the rapid development of nanotechnology and widespread use of nanoproducts, the ecotoxicity of nanoparticles (NPs) and their potential hazards to the environment have aroused great concern. Nanoparticles have increasingly been released into aquatic environments through various means, accumulating in aquatic organisms through food chains and leading to toxic effects on aquatic organisms. Nanoparticles are mainly classified into nano-metal, nano-oxide, carbon nanomaterials and quantum dots according to their components. Different NPs may have different levels of toxicity and effects on various aquatic organisms. In this paper, algae are used as model organisms to review the adsorption and distribution of NPs to algal cells, as well as the ecotoxicity of NPs on algae and fate in a water environment, systematically. Meanwhile, the toxic effects of NPs on algae are discussed with emphasis on three aspect effects on the cell membrane, cell metabolism and the photosynthesis system. Furthermore, suggestions and prospects are provided for future studies in this area.